(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
This study aims to find out the accuracy of PlanetScope imagery in analyzing the total content of Nitrogen (N), Phosphorus (P), Potassium (K) and Sulfur (S) in terrace paddy field. The area for this research is terraced paddy fields in Wonosari Sub-district, Gondangrejo District, Karanganyar Regency, Central Java Province, Indonesia. Aerial photo analysis from PlanetScope (www.planet.com) was conducted at the Pedology Laboratory and Soil Survey, while soil sample analysis was carried out at the Laboratory of Chemistry and Soil Fertility, Faculty of Agriculture, Sebelas Maret University (UNS). The preparation aerial photo analysis from PlanetScope was carried out in September 2019. Soil sampling, laboratory analysis, and data analysis were carried out from September 2019 to January 2020. There are 3 Citra PlanetScope bands that have a significant effect on the elements being studied. Those three bands are band 1 (red), band 3 (blue) and band 4 (NIR). Multiple linear regression analysis obtained a regression equation model from those three bands. This model can be used as an estimator for the existence of the soil nutrient being studied. The accuracy values obtained for N, P, K and S in terraced paddy fields are 97.58%; 94.85%; 85.97%; and 97.39% and the R2 value of 0.39; 0.30; 0.30 and 0.27. The R2 value, which is still relatively small, indicates that there are many factors may affect the accuracy value. Int. J. Agril. Res. Innov. Tech. 11(1): 1-9, June 2021